Co-movement and performance of conventional and Islamic stock markets in selected countries - Sahabuddin, Mohammad (2020)
Globalization is a dynamic and multi-dimensional integrated process of changing and moving of financial markets all over the world. It creates interdependency and cross countries linkages among the global financial villages. Particularly, financial markets integration and interconnection influence the level of co-movement and performance of stock markets. Due to the complex interrelationship among the different markets, it is difficult to assess the optimum level of co-movement and performance of particular stock markets. Moreover, globalized and highly integrated markets may lead to narrower pricing gaps and make vulnerable to different equity markets in responding global shocks. However, the latest incidents such as Arab spring revolutions (2010), Grexit (Greece’s potential withdrawal from the Eurozone 2012), Brexit (Britain’s withdrawal from the Eurozone, 2016), and Donald Trump’s presidency in USA (2017) have heightened tensions of further challenges in world economy. Apart from these, the recent trade war between two giant economies, namely the USA and China have made the issues more vulnerable, seem have caused a panic, and create a fear for future economic crisis in the world financial markets, with persistent magnitudes for future investment decision and investment strategists. In many developed and developing countries, Islamic (Shariah compliant) stock market has experienced rapid growth, and work in parallel with the mainstream conventional markets. Moreover, Islamic stock markets have come into shed on light as viable alternatives investment horizons with some distanced features that have been considered to be strong and show more resiliencies than conventional counterpart in responding to the shocks in recent financial crisis. Therefore, stock markets co-movement and performances are contentious issues that play crucial role in diversification, which is a standard risk management tool in any portfolio. The objectives of the study are three fold: a) to examine the co-movement, b) to compare the performance, and c) to investigate the reaction to financial crises of Islamic and conventional stock markets in selected developed and developing nations. Daily data are downloaded from Thomson Reuters DataStream, which covered six developed and developing countries, namely the United States, United Kingdom, Japan, Malaysia, Indonesia and China for the period of 26 October 2007 to 7 June 2018. A set of wavelet analysis techniques, which is established as superior tools in analyzing co-movement and performance are employed in this study. Additionally, the study uses multivariate generalized autoregressive conditional heteroscedasticity with dynamic conditional correlation to measure the reactions of stock markets during the recent crisis. Along with these advanced models, unit root test, Johnsen co-integration test and Vector error correction model approaches are also carried out. The research findings show that the Islamic stock markets move together with conventional counterpart but the level of co-movement depends on time and frequency domain properties in different stock markets. Chinese composite equity market (the Shanghai Stock Exchange Composite Index) particularly shows lower level co-movement and offers portfolio diversification opportunity in all investment horizons and scales, but China Islamic index offers portfolio benefits only in short-term holding period (D1 and D2 scales). Apart from this, the evidences of the wavelet based decomposed and cross correlation show that the Islamic markets are more dominant than conventional stock markets, except from the UK perspectives of both developed and developing nations. This finding implies that Islamic stock markets perform better than traditional based composite markets in long and mid-term holding period. Furthermore, high (low) volatility has been observed in Chinese and Malaysia Islamic stock index returns respectively during the global financial crisis in 2008. The implications of this study offer a fresh insight about co-movement and performances of conventional and Islamic stock markets and thus, making the international investors understand the heterogeneity of investment horizons (i.e., short, medium and long-term investment) easily.